Strings of Unity isang pag-aaral ng International Rondalla Festival (Cuerdas) bilang pamamahala sa sining sa Pilipinas - Vitto, Loen (Musika Jornal, 2022)
“Strings of Unity: Isang Pag-aaral ng International Rondalla Festival (Cuerdas) Bilang Pamamahala sa Sining sa Pilipinas” is a preliminary study on the concepts and ideas of arts management in the Philippines as a discipline. These ideas and concepts shall be presented through the process of management of the Strings of Unity: The International Rondalla Festival, or commonly known as Cuerdas — a music festival featuring plucked string instruments which includes the Philippine rondalla and other plucked string instruments from around the world.